2018
DOI: 10.1140/epjc/s10052-018-6074-8
|View full text |Cite
|
Sign up to set email alerts
|

FRW type Kaluza–Klein modified holographic Ricci dark energy models in Brans–Dicke theory of gravitation

Abstract: In this paper, we investigate non-Ricci, noncompact Friedmann-Robertson-Walker type Kaluza-Klein cosmology in the presence of pressureless matter and modified holographic Ricci dark energy in the frame work of Brans and Dicke (Phys Rev 124:965, 1961) scalar-tensor theory of gravitation. We solve the field equations of this theory using a hybrid expansion law for the five dimensional scale factor. We have also used a power law and a form of logarithmic function of the scale factor for the Brans-Dicke scalar fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…The most of the authors who have analyzed some cosmological models with dark energy both in general relativity and modified theories of gravitation, some of them are mentioned in Ref. Shekh, 2015, Chirde andShekh, 2018a;Bhoyar et al, 2017;Shekh and Chirde 2020); Naidu et al, 2012;Sarkar and Mahanta 2013;Kiran et al, 2015;Santhi et al, 2017;Aditya and Reddy, 2018). The reconstruction phenomenon of a well-known PDE model with f(G) gravity in the presence of power law scale factor Jawad and Rani, (2015) have reconstructed f(G) models with respect to two values of PDE parameter; that is, u = 2, −2 and checked the significant cosmological aspects of these reconstructed models while Jawad et al (2016a); Jawad et al (2017) studied the cosmological consequences of pilgrim dark energy model in the framework of generalized teleparallel gravity by considering the reconstruction scheme for f(T) models with power law scale factor taking Hubble horizon and Nojiri-Odintsov length as infrared cut-offs also observed that the Hubble parameter lies within observational suggested ranges while deceleration parameter represents the accelerated expansion behaviour of the Universe and the model corresponds to the quintessence region and phantom region for different cases of pilgrim dark energy parameter u under pilgrim dark energy models in fractal Universe while very recently Shekh, (2021a) analyzed the dynamical investigation of different models of holographic dark energy using Friedman-Lemâitre-Robertson-Walker cosmological model in the context of same f(Q) gravity by governing the features of the model in view of the relation between cosmic time and redshift which yields a purely accelerating evolving Universe.In order to obtain the analytic solution, consider the following form of dimensionless scale factor as of the form:…”
Section: Frw Universe With Interacting Soursementioning
confidence: 99%
“…The most of the authors who have analyzed some cosmological models with dark energy both in general relativity and modified theories of gravitation, some of them are mentioned in Ref. Shekh, 2015, Chirde andShekh, 2018a;Bhoyar et al, 2017;Shekh and Chirde 2020); Naidu et al, 2012;Sarkar and Mahanta 2013;Kiran et al, 2015;Santhi et al, 2017;Aditya and Reddy, 2018). The reconstruction phenomenon of a well-known PDE model with f(G) gravity in the presence of power law scale factor Jawad and Rani, (2015) have reconstructed f(G) models with respect to two values of PDE parameter; that is, u = 2, −2 and checked the significant cosmological aspects of these reconstructed models while Jawad et al (2016a); Jawad et al (2017) studied the cosmological consequences of pilgrim dark energy model in the framework of generalized teleparallel gravity by considering the reconstruction scheme for f(T) models with power law scale factor taking Hubble horizon and Nojiri-Odintsov length as infrared cut-offs also observed that the Hubble parameter lies within observational suggested ranges while deceleration parameter represents the accelerated expansion behaviour of the Universe and the model corresponds to the quintessence region and phantom region for different cases of pilgrim dark energy parameter u under pilgrim dark energy models in fractal Universe while very recently Shekh, (2021a) analyzed the dynamical investigation of different models of holographic dark energy using Friedman-Lemâitre-Robertson-Walker cosmological model in the context of same f(Q) gravity by governing the features of the model in view of the relation between cosmic time and redshift which yields a purely accelerating evolving Universe.In order to obtain the analytic solution, consider the following form of dimensionless scale factor as of the form:…”
Section: Frw Universe With Interacting Soursementioning
confidence: 99%
“…where φ 1 , β 1 > 1 and β 2 > 0 are constants. Recently, Singh and Kumar [95], Sadri and Vakili [96], and Aditya and Reddy [97] have investigated holographic DE models in BD theory using this logarithmic law for scalar field.…”
Section: Tsallis Holographic Dark Energy In Bd Theorymentioning
confidence: 99%
“…Planck Collaboration [4] results of cosmological parameters show different types of dark energy like ᴧCDM and SCDM. In Brans-Dicke (B-D) theory [5] context many works [6][7][8][9][10][11][12][13] on cosmological models are going on for a long time and the results show the supportive evidence with observational data. Different researchers [14][15][16][17] have also worked a lot on cosmological models with electromagnetic fields.…”
Section: Introductionmentioning
confidence: 98%